Quality by design (QBD) approach to develop hplc method for ritonavir: application to hydrolytic, thermal, oxidative and photolytic degradation kinetics (Funded Work) - PALLAVI MANGESH PATIL (International Journal of Pharma and Bio Sciences, 2017)
Stability of Ritonavir (RITO) was investigated using a stability indicating reverse phase high-performance liquid chromatography (RP-HPLC) method. Experimental designs were applied for multivariate optimization of the experimental conditions of (RP-HPLC) method. Three independent factors: methanol content in the mobile phase composition, buffer pH and flow rate were used to design mathematical models. Quality by Design (QbD) approach was used to facilitate method development. RITO was exposed to different stress conditions, including hydrolytic (acid, base, neutral), oxidative, thermal and photolytic. Relevant degradation was found to take place in all the conditions. The degradation of RITO followed (pseudo) first-order kinetics under experimental conditions. Using this optimum condition, baseline separation of both drugs with good resolution and a run time of less than 7 min were achieved. The kinetic parameters (rate constant, t1/2, and t90) of the degradation of RITO were calculated. The optimized assay condition was validated according to ICH guidelines to confirm specificity, linearity, accuracy and precision.